Interculture-Based Language Learning Model to Improve Prospective English Teachers’ Speaking Skills Viewed From Linguistic Awareness - Haerazi; Irawan, Lalu Ari; Sotlikova, Rimajon (JEELS (Journal of English Education and Linguistics Studies), 2023)
This study aimed to know the use of the interculture-based language learning (IBLL) model to improve learners’ speaking skills integrated with linguistic awareness and their responses to learning experiences. A mixed-method study was employed, employing the concurrent embedded design, to investigate the learning processes associated with the IBLL model in enhancing speaking skills. The data consisted of qualitative and quantitative data. The qualitative data were collected using observation sheets and interviews, while the qualitative data were attained using tests. The finding showed that the IBLL model facilitates learners to improve grammar competence, vocabulary acquisition, fluency, pronunciation, and description detail. The speaking improvement of learners was affected with learners’ linguistic awareness. Based on this, learners have positive responses to the use of the IBLL model in the speaking class. This study can be concluded that the use of the IBLL model was able to improve speaking skills viewed from linguistic awareness. The implication of the current study acknowledges that language learning goes beyond mere linguistic competence and it entails an exploration of cultural nuances, social contexts, and the interconnectedness between language and societal practices.